A battery and an electric device

CN123018086APending Publication Date: 2026-10-30SHENZHEN HIGHPOWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611510569.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]针对全硅电池电解液体系长期电化学稳定性差、循环过程界面副反应严重、电池容量衰减快的问题,本发明提供了一种电池及用电装置

Benefits of technology

[0016]根据本发明提供的电池,通过协同调控正极活性物质中铝的含量与电解液中共溶剂与添加剂的含量,并限定其比值满足0.03≤X/(A+B)≤0.035,实现正极本体结构稳定改性与电解液界面成膜保护的精准匹配协同。正极中适量掺杂/包覆的铝元素能够稳定正极晶格,抑制充放电过程中正极相变、晶格畸变与活性物质粉化脱落,从电极源头减少界面副反应诱因;电解液体系内异氰酸酯类硅烷共溶剂与环状羰基类添加剂复配,可在正负极表面协同构筑兼具高离子电导率、高机械强度与优异柔韧性的复合SEI/CEI膜,阻隔电极与电解液直接接触、缓冲电极体积膨胀、降低电解液持续分解损耗。通过限定X与A+B的比例区间,使正极铝改性带来的结构稳定能力和电解液双组分的界面防护能力形成动态平衡:既不会出现铝含量偏低、正极结构易劣化,无法匹配电解液成膜保护效果的问题;也不会出现电解液功能性成膜组分不足、界面膜防护失效,难以适配高铝改性正极界面特性的缺陷。三者参数相互适配、增益叠加,有效降低电池整体界面阻抗,减少不可逆容量损失,大幅提升电池长循环容量保持率,同时抑制高温存储过程中的产气、容量衰减现象,同步优化电池循环寿命与高温存储性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a battery and a power utilization device, comprising: a positive electrode sheet, the positive electrode sheet comprising a positive electrode active material, the positive electrode active material being doped and / or coated with an aluminum element; the mass content of the aluminum element being X %; an electrolyte comprising a cosolvent and an additive; the cosolvent comprising a cyclic carbonyl compound, and the additive comprising an isocyanate silane compound; the mass percentage of the cosolvent in the electrolyte being denoted as A %; the mass percentage of the additive in the electrolyte being denoted as B %; 0.03 <= X / (A+B) <= 0.035; by limiting the ratio range of X and A+B, the structural stability ability brought by the positive electrode aluminum modification and the interface protection ability of the two components of the electrolyte form a dynamic balance: the three parameters are mutually adapted and the gains are superimposed, the overall interface impedance of the battery is effectively reduced, the irreversible capacity loss is reduced, the long cycle capacity retention rate of the battery is greatly improved, the gas production and capacity attenuation phenomena in the high-temperature storage process are inhibited, and the cycle life and high-temperature storage performance of the battery are simultaneously optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically to a battery and an electrical device. Background Technology

[0002] Silicon-based anodes, with their ultra-high theoretical specific capacity, are a core candidate anode material for high-energy-density lithium-ion batteries. However, the massive volume expansion of silicon materials during charging and discharging continuously damages the electrode / electrolyte interface, leading to extensive electrolyte decomposition and active material pulverization and shedding, severely limiting battery cycle and storage life. Therefore, the industry has conducted extensive research and development on all-silicon electrolytes adapted to silicon-based anodes, and related developments have made phased progress at the level of solvent and additive molecular structure design.

[0003] In the development of electrolyte solvents, current research mainly focuses on novel solvent systems with high stability and wide electrochemical windows, such as various functionalized ionic liquids. These systems rely on special molecular structures to broaden the electrolyte's withstand voltage range and mitigate the redox decomposition behavior of solvents on high-potential, high-strain electrode surfaces. In the field of additive development, existing technologies mostly employ various film-forming additives. These additives preferentially decompose to construct a solid electrolyte interfacial film on the electrode surface, reducing direct contact between the electrolyte and the active sites of the silicon anode through physical isolation, thereby weakening irreversible interfacial side reactions.

[0004] Although existing solvent and additive molecular design schemes for all-silicon electrolytes can improve the interface state of silicon anodes to some extent, this type of electrolyte system still suffers from key technical defects that are difficult to overcome. First, the overall long-term electrochemical stability of the electrolyte is insufficient. Under the interfacial stress impact caused by repeated volume deformation of the silicon anode, the interfacial film is prone to cracking and peeling. The electrolyte will continuously react with the fresh electrode surface, causing rapid capacity decay and a continuous increase in internal resistance. Second, there is a lack of quantitative synergistic matching design between existing solvent and additive components. Simply adjusting the solvent or additive content is insufficient to simultaneously ensure cathode lattice stability and long-term protection of the cathode-anode interface. Under long-cycle, high-temperature storage conditions, side reactions continue to intensify. Third, the existing high-stability ionic liquid solvents and special functional film-forming additives have complex synthesis routes and high raw material prices, resulting in high costs for large-scale production. Furthermore, the supporting electrolyte preparation and purification processes are not yet mature, making large-scale industrial application difficult. Therefore, overcoming these technical problems and defects is a key issue that needs to be addressed. Summary of the Invention

[0005] To address the problems of poor long-term electrochemical stability, severe interfacial side reactions during cycling, and rapid capacity decay in all-silicon battery electrolyte systems, this invention provides a battery and an electrical device.

[0006] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: In one aspect, the present invention provides a battery comprising: A positive electrode sheet, comprising a positive current collector and a positive active material layer disposed on the positive current collector, the positive active material layer comprising a positive active material, the positive active material being doped with and / or coated with aluminum; the mass content of aluminum in the positive active material layer is X %, the value of X being in the range of 0.1-1; A negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer disposed on both sides of the negative electrode current collector, the negative electrode active material layer comprising pure silicon particles; An electrolyte comprising a co-solvent and an additive; the co-solvent comprising a cyclic carbonyl compound, and the additive comprising an isocyanate silane compound; wherein the total mass of the electrolyte is denoted as 100%, the mass percentage of the co-solvent in the electrolyte is denoted as A%, where A ranges from 2 to 20; and the mass percentage of the additive in the electrolyte is denoted as B%, where B ranges from 0.5 to 2. The values ​​of A, B, and X satisfy the following conditions: 0.03≤X / (A+B)≤0.035.

[0007] Optionally, the value of A is in the range of 5-10.

[0008] Optionally, the value of B is in the range of 0.8-1.

[0009] Optionally, the cyclic carbonyl compound includes one or more of cyclopentanone, 1,4-butyrolactone, ethylene carbonate, 3-cyclopenten-1-one, and vinylene carbonate.

[0010] Optionally, the chemical formula of the isocyanate silane compound is: Si(OR1)3-(R2)3-NCO; R1 and R2 are each independently selected from one of the C1-C6 alkyl groups.

[0011] Optionally, the isocyanate silane compound includes one or more of 3-isocyanate propyltriethoxysilane and 3-isocyanate propyltrimethoxysilane.

[0012] Optionally, the electrolyte further includes a lithium salt, which includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxaloyl)borate, lithium difluorophosphate, lithium difluorooxaloylborate, lithium difluorodioxaloyl phosphate, lithium tetrafluorooxaloyl phosphate, lithium tri(oxaloyl)phosphate, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide.

[0013] Optionally, the electrolyte further includes a solvent, which includes one or more of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, γ-butyrolactone, and δ-valerolactone.

[0014] Optionally, the pure silicon particles are deposited on the surface of the negative electrode current collector to form the negative electrode active material layer.

[0015] Another aspect of the present invention provides an electrical device comprising the battery described above.

[0016] According to the battery provided by the present invention, by synergistically controlling the content of aluminum in the positive electrode active material and the content of co-solvent and additives in the electrolyte, and limiting their ratio to satisfy 0.03≤X / (A+B)≤0.035, a precise matching and synergistic effect is achieved between the stable modification of the positive electrode structure and the interfacial film protection of the electrolyte. Appropriate doping / coating of aluminum in the positive electrode can stabilize the positive electrode lattice, suppress phase transitions, lattice distortion, and active material pulverization and shedding during charging and discharging, reducing the inducing factors of interfacial side reactions from the electrode source. The combination of isocyanate-based silane co-solvents and cyclic carbonyl additives in the electrolyte system can synergistically construct a composite SEI / CEI film with high ionic conductivity, high mechanical strength, and excellent flexibility on the positive and negative electrode surfaces, preventing direct contact between the electrode and the electrolyte, buffering electrode volume expansion, and reducing continuous electrolyte decomposition losses. By limiting the ratio range of X and A+B, a dynamic balance is achieved between the structural stability brought about by aluminum modification of the cathode and the interfacial protection capability of the two-component electrolyte. This avoids the problems of low aluminum content leading to easy degradation of the cathode structure and inability to match the film-forming protection effect of the electrolyte; and also avoids the defects of insufficient functional film-forming components in the electrolyte, resulting in interface film protection failure and inability to adapt to the interface characteristics of high-aluminum modified cathodes. The three parameters are mutually adapted and their gains are superimposed, effectively reducing the overall interface impedance of the battery, reducing irreversible capacity loss, significantly improving the battery's long-cycle capacity retention rate, and suppressing gas generation and capacity decay during high-temperature storage, thus simultaneously optimizing battery cycle life and high-temperature storage performance. Detailed Implementation

[0017] To make the technical problems solved, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.

[0018] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; the materials and reagents used are commercially available unless otherwise specified.

[0019] In one embodiment, the present invention provides a battery comprising: A positive electrode sheet, comprising a positive current collector and a positive active material layer disposed on the positive current collector, the positive active material layer comprising a positive active material, the positive active material being doped with and / or coated with aluminum; the mass content of aluminum in the positive active material layer is X %, the value of X being in the range of 0.1-1; A negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer disposed on both sides of the negative electrode current collector, the negative electrode active material layer comprising pure silicon particles; An electrolyte comprising a co-solvent and an additive; the co-solvent comprising a cyclic carbonyl compound, and the additive comprising an isocyanate silane compound; wherein the total mass of the electrolyte is denoted as 100%, the mass percentage of the co-solvent in the electrolyte is denoted as A%, where A ranges from 2 to 20; and the mass percentage of the additive in the electrolyte is denoted as B%, where B ranges from 0.5 to 2. The values ​​of A, B, and X satisfy the following conditions: 0.03≤X / (A+B)≤0.035.

[0020] Specifically, the value of X is any one value or a range of any two values ​​from 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0; in a preferred embodiment, the value of X is 0.3-0.7.

[0021] When the value of X is in the range of 0.1-1, the aluminum doped / coated in the positive electrode active material can be uniformly distributed on the surface and inside the crystal lattice of the positive electrode active material. The modification effect of aluminum can effectively stabilize the positive electrode crystal structure, suppress the phase transition collapse and crystal distortion of the positive electrode material during battery charge and discharge cycles, and reduce the pulverization and shedding of the positive electrode active material. At the same time, an appropriate amount of aluminum can optimize the microstructure of the positive electrode interface, reduce the positive electrode interface impedance, and form a stable positive electrode interface film in conjunction with the electrolyte system, significantly reducing interface side reactions during high-temperature storage and long-cycle processes, and significantly improving the cycle life and storage stability of the battery. When the value of X is less than 0.1, the amount of aluminum doped / coated in the positive electrode active material is too low, and its modification and stabilization effect on the positive electrode crystal lattice is extremely limited, and it cannot effectively suppress the structural collapse and phase transition cracking of the positive electrode material during charge and discharge processes. After long-term cycling, the positive electrode active material is prone to extensive pulverization and shedding, resulting in numerous defects at the positive electrode interface. This prevents the formation of a stable and synergistic interface structure with the electrolyte system, leading to frequent interface side reactions. Consequently, battery capacity rapidly declines, cycle life is significantly shortened, and electrolyte decomposition intensifies during high-temperature storage, exacerbating gas generation and capacity drops. When the value of X is greater than 1, the aluminum content on the positive electrode surface and in the crystal lattice is excessive. Excessive aluminum covers a large number of electrochemical active sites in the positive electrode active material, hindering the insertion and extraction of lithium ions, significantly increasing the positive electrode interface impedance, and reducing the battery's charge / discharge efficiency and rate performance. Furthermore, excessive aluminum tends to form an excessively thick inert coating layer on the positive electrode surface, disrupting the compatibility between the positive electrode interface and the electrolyte. This results in uneven interface film thickness and decreased stability, further exacerbating local side reactions, leading to increased battery polarization, insufficient capacity utilization, and deterioration in both cycle and storage performance.

[0022] Specifically, the cyclic carbonyl structure of the cosolvent possesses moderate dielectric constant and electrochemical stability, which can effectively optimize the solvation structure of the electrolyte, promote the full dissociation of lithium salt, improve the overall ionic conductivity of the electrolyte, and reduce the lithium-ion migration barrier. Simultaneously, the cyclic carbonyl cosolvent can assist in film formation at the electrode interface, fill interfacial micro-defects, optimize the uniformity and density of the interfacial film, and synergistically construct a stable composite SEI / CEI interface system with isocyanate-based silane additives. This effectively suppresses electrolyte decomposition and electrode interfacial side reactions. Combined with the lattice stabilizing effect of the aluminum-modified cathode, it significantly improves the battery's long-cycle stability and high-temperature storage performance.

[0023] Specifically, the value of A is any one point value or any two point values ​​from 2, 4, 6, 8, 10, 12, 14, 16, 18 or 20.

[0024] When the value of A is in the range of 2-20, the co-solvent can fully exert its role in solvent regulation and film formation assistance, effectively suppressing electrolyte decomposition and electrode interface side reactions. Combined with the lattice stabilizing effect of aluminum-modified cathode, it significantly improves the battery's long-cycle stability and high-temperature storage performance. When the value of A is less than 2, the amount of cyclic carbonyl co-solvent added is too low, making it difficult to assist in film formation and repair interface defects. The interface protection capability is greatly reduced, the electrolyte continues to undergo redox decomposition, the cathode transition metal dissolution and interface oxygen evolution side reactions are aggravated, resulting in increased irreversible capacity loss of the battery, accelerated long-cycle decay rate, and prominent problems of gas generation and capacity drop during high-temperature storage. When the value of A is greater than 20, excessive cyclic carbonyl components are prone to excessive accumulation and excessive participation in film formation at the electrode interface, resulting in uneven interfacial film thickness and a surge in impedance. This leads to a decrease in the flexibility and structural stability of the interfacial film, making it prone to failure during long-term cycling, ultimately significantly deteriorating the battery's cycle life and high-temperature storage safety.

[0025] The additive includes isocyanate groups (-N=C=O) and silane groups (-Si(OR)3). During the first charge-discharge and formation processes of the battery, this additive preferentially undergoes reduction reactions on the negative electrode surface or reacts with the active sites on the surface to generate a polymer interface film rich in nitrogen and silicon. This imparts excellent ionic conductivity to the SEI film, effectively promoting rapid lithium-ion insertion and extraction. Simultaneously, the high mechanical extensibility of the polymer network effectively buffers the volume expansion of the electrodes, especially the silicon-based negative electrode, during charge-discharge cycles, preventing continuous reduction and decomposition of the electrolyte at the negative electrode interface. Furthermore, the silane groups (-Si(OR)3) in the additive can undergo specific coordination and chemical coupling anchoring reactions with the metal oxides on the positive and negative electrode surfaces, constructing a dense and stable protective layer at the electrode interface. This fundamentally prevents direct contact between the electrode active materials and the electrolyte, significantly reducing the rate of interfacial side reactions. In addition, the alkoxy groups in the silane group can undergo in-situ hydrolysis and condensation reactions in the electrolyte system to form a stable siloxane inorganic network, which serves as the inorganic framework of the SEI / CEI membrane. This significantly improves the mechanical strength and structural integrity of the interfacial membrane, preventing problems such as cracking, shedding, and repeated film formation during long-term charge-discharge cycles.

[0026] Specifically, the value of B is any one value or any two values ​​from 0.5, 0.8, 1, 1.2, 1.5, 1.8 or 2.

[0027] When the value of B is in the range of 0.5-2, appropriate addition can completely cover the electrode active sites, effectively suppress interfacial side reactions and electrolyte decomposition, and avoid the problems of excessive component agglomeration and increased internal resistance, thus maximizing the synergistic improvement of battery cycle performance and high-temperature storage performance. When the value of B is less than 0.5, the siloxane inorganic framework and nitrogen-containing polymer network are not fully formed, the interfacial film has a large number of microscopic defects, the interfacial side reactions cannot be effectively suppressed, the electrolyte continues to decompose and consume, the electrode active materials continue to deteriorate, the battery capacity decays rapidly, and the cycle life and high-temperature storage stability are significantly reduced. When the value of B is greater than 2, excessive additives will decompose and accumulate excessively at the electrode interface, forming an excessively thick interfacial film, which significantly increases the lithium-ion transport impedance and deteriorates the battery kinetic performance. In addition, excessive silane groups are prone to excessive cross-linking, resulting in increased brittleness and decreased flexibility of the interfacial film, which cannot adapt to the volume deformation during electrode cycling. It is prone to cracking and detachment during long-term cycling, inducing continuous interfacial side reactions and electrolyte decomposition, which seriously reduces the cycle reliability and high-temperature storage performance of the battery.

[0028] Specifically, the value range of X / (A+B) is any one value or a range of any two values ​​among 0.03, 0.031, 0.032, 0.033, 0.034, and 0.035; in a preferred embodiment, the value range of X / (A+B) is 0.032-0.034.

[0029] When the value of X / (A+B) is in the range of 0.03-0.035, a precise synergistic relationship is formed between the amount of aluminum element modification in the cathode, the amount of co-solvent and additive added in the electrolyte, and the appropriate amount of aluminum element stabilizes the cathode bulk structure and inhibits cathode phase transition and pulverization. The appropriate ratio of co-solvent and additive forms a highly ion-conductive and mechanically stable SEI / CEI film at the electrode interface, blocking interfacial side reactions and buffering electrode volume deformation. The precise matching of these three parameters avoids the performance defects caused by excessive or insufficient single parameters, and maximizes the synergistic effect of structural modification and interface modification, significantly reducing the overall interface impedance of the battery, inhibiting the continuous decomposition of the electrolyte and the loss of active materials, and significantly improving the battery's long-cycle capacity retention rate and high-temperature storage stability. When the value of X / (A+B) is less than 0.03, the content of aluminum element modification in the cathode is relatively low relative to the total amount of film-forming functional components in the electrolyte, and cannot match the interface protection capability of the electrolyte system. Even if the electrolyte can form a high-quality composite interfacial film, the cathode material itself is still prone to charge-discharge phase transitions, lattice cracking, and active material shedding. The shed active material continuously damages the interfacial film structure, inducing subsequent interfacial side reactions, leading to accelerated overall battery cycle degradation. This prevents the full utilization of the electrolyte film-forming system's performance advantages, resulting in the failure of the overall performance synergistic gain effect. When the value of X / (A+B) is greater than 0.035, the aluminum modification content of the cathode is too high relative to the total amount of electrolyte film-forming components. Excessive aluminum modification components easily cause a high cathode interfacial impedance. At the same time, the content of co-solvents and additives in the electrolyte is relatively insufficient, making it impossible to form a sufficient, complete, and stable interfacial film at the electrode interface, which is difficult to match the interfacial characteristics of the high-aluminum modified cathode. The electrolyte's protection ability for the electrode interface is insufficient, failing to effectively block the side reactions between the electrode and the electrolyte. The interfacial film is easily damaged and fails. Meanwhile, the impedance problem caused by the high-aluminum modification of the cathode becomes prominent, hindering lithium-ion transport. Ultimately, this leads to increased battery polarization, limited capacity utilization, and the inability to achieve optimal cycle and storage performance.

[0030] In some embodiments, the types of positive electrode active materials mentioned in this invention are not limited, and any known positive electrode active material can be used.

[0031] In some embodiments, the positive electrode active material mentioned in this invention includes at least one of lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), ternary materials (NCM / NCA), lithium-rich manganese-based materials, and lithium nickel oxide (LiNiO2).

[0032] In one embodiment, the positive electrode active material layer further includes a positive electrode conductive agent and a positive electrode binder.

[0033] In some embodiments, the type of positive conductive agent mentioned in this invention is not limited, and any known conductive agent can be used.

[0034] In some embodiments, the positive electrode conductive agent mentioned in this invention includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene.

[0035] In one embodiment, the type of positive electrode binder mentioned in this invention is not limited, and any known positive electrode binder can be used.

[0036] In some embodiments, the positive electrode binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.

[0037] In some embodiments, the type of positive electrode current collector is not particularly limited, as long as it can achieve the purpose of this application. The specific positive electrode current collectors that can be selected include, but are not limited to, copper foil and aluminum foil. Among them, aluminum foil is the preferred choice because it has good conductivity, excellent corrosion resistance and suitable mechanical strength. In addition, nickel-plated copper foil, conductive polymer current collectors, etc. can also be selected.

[0038] In some embodiments, there are no particular restrictions on the negative electrode current collector, as long as it can achieve the purpose of this application. The specific negative electrode current collectors that can be selected include, but are not limited to, copper foil, nickel-plated copper foil, conductive polymer current collectors, etc.

[0039] In some preferred embodiments, the negative current collector comprises copper foil.

[0040] In one embodiment, a separator is also included, which is located between the positive electrode and the negative electrode.

[0041] This application does not impose any particular restrictions on the material and shape of the diaphragm, as long as it does not significantly impair the effectiveness of this application.

[0042] In some embodiments, the diaphragm includes at least one of polyethylene (PE), polypropylene (PP), PP / PE / PP three-layer composite diaphragm, ceramic-coated diaphragm, aramid, polyimide (PI), and nonwoven fabric diaphragm.

[0043] In some embodiments, the lithium-ion battery may include an outer packaging that can be used to encapsulate the electrode assembly and electrolyte described above.

[0044] The battery provided by this invention achieves precise matching and synergy between the stable modification of the cathode structure and the content of co-solvents and additives in the electrolyte by synergistically controlling the aluminum content in the positive electrode active material and the content of co-solvents and additives in the electrolyte, and limiting their ratio to 0.03≤X / (A+B)≤0.035. Appropriate doping / coating of aluminum in the positive electrode can stabilize the cathode lattice, suppress phase transitions, lattice distortion, and active material pulverization and shedding during charging and discharging, reducing the inducing factors of interfacial side reactions from the electrode source. The combination of isocyanate-based silane co-solvents and cyclic carbonyl additives in the electrolyte system can synergistically construct a composite SEI / CEI film with high ionic conductivity, high mechanical strength, and excellent flexibility on the surfaces of the positive and negative electrodes, preventing direct contact between the electrodes and the electrolyte, buffering electrode volume expansion, and reducing continuous electrolyte decomposition losses. By limiting the ratio range of X and A+B, a dynamic balance is achieved between the structural stability brought about by aluminum modification of the cathode and the interfacial protection capability of the two-component electrolyte. This avoids the problems of low aluminum content leading to easy degradation of the cathode structure and inability to match the film-forming protection effect of the electrolyte; and also avoids the defects of insufficient functional film-forming components in the electrolyte, resulting in interface film protection failure and inability to adapt to the interface characteristics of high-aluminum modified cathodes. The three parameters are mutually adapted and their gains are superimposed, effectively reducing the overall interface impedance of the battery, reducing irreversible capacity loss, significantly improving the battery's long-cycle capacity retention rate, and suppressing gas generation and capacity decay during high-temperature storage, thus simultaneously optimizing battery cycle life and high-temperature storage performance.

[0045] In one embodiment, the value of A is in the range of 5-10.

[0046] Within this range, cyclic carbonyl cosolvents can precisely control the lithium-ion solvation structure of the electrolyte, reduce the lithium-ion insertion / extraction barrier, and fully fill the micropores of the interface film formed by the cosolvent, further improving the density of the protective film. The cosolvent has no excessive free residue, will not cause side reactions or high-temperature gas generation in the electrolyte, and can work synergistically with isocyanate silane additives to reduce irreversible interface losses. When matched with a cosolvent system in the 5-10 content range, it can further reduce the interface impedance, stabilize the electrode interface state, and significantly improve the battery capacity retention rate.

[0047] In one embodiment, the value of B ranges from 0.8 to 1.

[0048] Within this range, the appropriate amount of isocyanate-based silane additives can fully release the dual film-forming effect of isocyanate groups and silane groups. The additives preferentially decompose to form a nitrogen-containing silicon polymer network and a siloxane inorganic framework, constructing a uniform and dense SEI / CEI film with both high ion conductivity and strong mechanical stability. This film can completely cover all active sites of the electrode, effectively buffering the volume expansion of the silicon-based negative electrode, anchoring the metal oxides on the electrode surface to suppress side reactions, and forming optimal compatibility with cyclic carbonyl cosolvents. This helps the cosolvents to improve the microstructure of the interfacial film, maximizing the synergistic improvement of the battery's long-cycle and high-temperature storage performance.

[0049] In one embodiment, the cyclic carbonyl compound includes one or more of cyclopentanone, 1,4-butyrolactone, ethylene carbonate, 3-cyclopenten-1-one, and vinylene carbonate.

[0050] In one embodiment, the cyclic carbonyl compound is cyclopentanone. Cyclopentanone possesses a suitable reduction potential and excellent electrolyte compatibility, which can effectively optimize the electrolyte solvation structure, promote the full dissociation of lithium salts, reduce the lithium-ion migration barrier, and improve battery kinetic performance. Simultaneously, cyclopentanone can synergistically participate in the modification and formation of the negative electrode SEI film, compensating for microscopic pore defects during the film formation process of silane additives and improving the uniformity of the SEI film.

[0051] In one embodiment, the cyclic carbonyl compound is 1,4-butyrolactone. 1,4-Butyrolactone possesses a high dielectric constant and excellent lithium salt solubility, which can significantly improve the ion conductivity of the electrolyte and enhance the low-temperature charge-discharge performance of the battery. Simultaneously, 1,4-butyrolactone can undergo a controlled ring-opening polymerization reaction on the negative electrode side, assisting isocyanate-based silane additives in constructing a composite SEI film and enhancing the flexibility of the negative electrode interface.

[0052] In one embodiment, the cyclic carbonyl compound is ethylene carbonate. Ethylene carbonate possesses excellent anode film-forming properties, undergoing a controllable single-electron reduction reaction on the anode surface to generate a dense, highly stable SEI film primarily composed of Li₂CO₃ and alkyl lithium carbonate. This effectively suppresses solvent co-intercalation and side reactions at the anode interface, matching the volume deformation characteristics of silicon-based anodes. In traditional systems, ethylene carbonate at high potentials exhibits weak oxidation resistance and is prone to oxidation and gas generation. This invention stabilizes the cathode lattice structure through aluminum modification, reducing surface oxygen activity. Simultaneously, it utilizes isocyanate-based silane additives to construct a dense CEI protective layer at the cathode interface, isolating the active sites of the cathode from direct contact with ethylene carbonate and effectively suppressing the oxidative decomposition and gas generation of ethylene carbonate at high potentials. This achieves simultaneous stabilization of the anode and cathode interfaces, significantly improving battery cycle life and safety.

[0053] In one embodiment, the cyclic carbonyl compound is 3-cyclopenten-1-one. The 3-cyclopenten-1-one molecule contains both a highly active C=O carbonyl group and a C=C carbon-carbon double bond, allowing it to participate in film formation at both the positive and negative electrode interfaces. On the negative electrode side, its active groups can undergo reductive polymerization to assist in constructing a flexible and stable SEI film and buffer the negative electrode volume expansion. On the positive electrode side, its C=C double bond can undergo controlled electrophilic polymerization under high voltage to form a dense polymer CEI film with a conjugated structure, effectively passivating the positive electrode lattice activity and suppressing transition metal dissolution and interfacial oxygen evolution side reactions. Traditional systems of 3-cyclopenten-1-one suffer from problems such as easy self-polymerization at high temperatures and uncontrollable film formation. This invention, by precisely limiting the ratio of X / (A+B), matches the stable structure of the aluminum-modified cathode with the anchoring framework system of the silane co-solvent. This allows for precise control of the degree of polymerization reaction, suppressing high-temperature self-polymerization failure and the problem of increased film impedance caused by over-polymerization, while retaining its excellent dual-interface film formation advantage and taking into account both battery dynamics performance and long-term cycle stability.

[0054] In one embodiment, the cyclic carbonyl compound is vinylene carbonate. Vinylene carbonate is an excellent interfacial film-forming aid. When used alone in this system, it preferentially undergoes reductive polymerization at the negative electrode to form a highly flexible SEI film rich in a polycarbonate crosslinked network. This film has moderate ionic conductivity and excellent electronic insulation, effectively inhibiting the continuous reductive decomposition of the electrolyte, alleviating the volume expansion of the negative electrode, and reducing the shuttle deposition of cobalt ions at the negative electrode. On the positive electrode side, it can undergo oxidative polymerization to form a crosslinked CEI film, effectively suppressing the oxidation and oxygen evolution side reactions of the positive electrode electrolyte. Traditional vinylene carbonate systems suffer from drawbacks such as easy decomposition of the high-temperature film and increased internal resistance. This invention improves the structural stability of the cathode by modifying the cathode with aluminum, and constructs a high-temperature resistant siloxane inorganic framework by combining an appropriate amount of isocyanate-based silane co-solvent. This effectively enhances the high-temperature stability of the vinylene carbonate organic film, inhibits polymer chain rearrangement and decomposition at high temperatures, and avoids the problem of increased internal resistance caused by excessive co-solvent by precisely controlling the amount A added and the ratio range. This significantly improves the high-temperature storage performance and long-cycle reliability of the battery.

[0055] In one embodiment, the chemical formula of the isocyanate silane compound is: Si(OR1)3-(R2)3-NCO; R1 and R2 are each independently selected from one of the C1-C6 alkyl groups.

[0056] This defined molecular structure possesses both stable silane alkoxy functional groups and highly active isocyanate end groups. Furthermore, the regular structure of the intermediate alkyl chain segment and the moderate carbon chain length make it highly compatible with the aluminum-modified cathode, cyclic carbonyl additive complex system, and the parameter ratio of 0.03≤X / (A+B)≤0.035 of this invention. The regular C1-C6 short alkyl chain exhibits excellent electrolyte solubility and dispersion uniformity, avoiding the molecular aggregation and electrolyte viscosity surge problems that are prone to occur with long carbon chains. This ensures efficient lithium-ion migration and maintains the battery's excellent kinetic performance. The Si(OR1)3 groups at the molecular ends can stably undergo hydrolysis-condensation reactions, generating a uniform siloxane inorganic framework in situ at the electrode interface. This framework forms a strong chemical anchoring effect with the metal oxides on the electrode surface, significantly improving the mechanical strength and structural stability of the interfacial film. The NCO isocyanate groups at the other end can efficiently participate in the interfacial polymerization film formation, generating a nitrogen- and silicon-rich polymer network with high ionic conductivity. This enhances the flexibility of the SEI / CEI film and effectively buffers volume deformation during electrode cycling. Simultaneously, the defined alkyl substitution structure allows for precise control of the compound's redox activity, ensuring its film formation rate is highly matched to the interfacial characteristics of the aluminum-modified cathode and the film formation rhythm of the cyclic carbonyl additive. This effectively avoids the problems of traditional silane compounds, such as excessively fast film formation leading to porous films or insufficient protection due to excessively slow film formation. It synergistically suppresses interfacial side reactions, electrolyte decomposition, and metal dissolution, further stabilizing the battery interface structure and significantly improving the battery's long-cycle performance and high-temperature storage stability.

[0057] In one embodiment, the isocyanate silane compound includes one or more of 3-isocyanate propyltriethoxysilane and 3-isocyanate propyltrimethoxysilane.

[0058] Both 3-isocyanate propyltriethoxysilane and 3-isocyanate propyltrimethoxysilane carry bifunctional functional groups of isocyanate group (-N=C=O) and silane alkoxy group (-Si(OR)3), which can be perfectly adapted to the aluminum modified cathode system, cyclic carbonyl single additive system and precise ratio of 0.03≤X / (A+B)≤0.035 of this invention. The synergistic effect of the bifunctional groups achieves efficient modification and stable protection of the electrode interface.

[0059] In one embodiment, the isocyanate silane compound is 3-isocyanatepropyltriethoxysilane. This compound carries an ethoxy group (-OCH2CH3), exhibiting moderate hydrolysis reactivity. During battery formation, it maintains a mild and controllable reaction rate, avoiding problems such as a loose interfacial film due to excessively rapid reaction or insufficient protection due to an excessively slow reaction. At the negative electrode interface, it undergoes stepwise hydrolysis-condensation and polymerization reactions to construct a unique "dense inside, sparse outside" gradient structure SEI film: the inner layer forms a dense siloxane inorganic network framework through ethoxy hydrolysis-condensation, effectively blocking electrolyte component penetration and inhibiting continuous electrolyte reduction and decomposition at the source; the outer layer generates a nitrogen- and silicon-rich organic polymer network from the isocyanate group reaction, possessing excellent mechanical ductility to effectively buffer the volume expansion during silicon-based negative electrode cycling, and also imparting high ionic conductivity to the interfacial film, constructing an efficient lithium-ion transport channel to ensure rapid lithium-ion insertion and extraction. Simultaneously, its silane groups can undergo specific chemical coupling and anchoring with the metal oxides on the positive and negative electrode surfaces, forming a stable interfacial protective layer and reducing the rate of interfacial side reactions. Under the parameter ratio system adapted to this invention, this compound can balance interfacial stability and battery kinetic performance, significantly improving the battery's high-rate charge-discharge capability, long-cycle performance, and high-temperature storage stability.

[0060] In one embodiment, the isocyanate silane compound is 3-isocyanatepropyltrimethoxysilane. The methoxy group (-OCH3) carried by this compound molecule exhibits stronger hydrolytic activity, allowing for rapid hydrolysis and condensation reactions in the electrolyte system. This preferentially forms a highly dense and structurally complete siloxane inorganic substrate film on the electrode surface, achieving rapid and comprehensive protection of the electrode interface. Furthermore, the isocyanate groups in the molecule undergo reduction polymerization at the electrode active sites, introducing highly conductive nitrogen-containing functional groups to modify the inorganic film layer, ultimately forming a high-density, structurally stable composite SEI / CEI interface film with good ion conductivity. The highly dense siloxane framework effectively resists strong oxidative stress under high-voltage conditions, significantly inhibiting the oxidative decomposition of the electrolyte and the degradation of electrode active materials at high potentials, and effectively reducing positive electrode metal dissolution and interfacial oxygen evolution side reactions. Combining the lattice stabilizing effect and precise parameter ratio of the aluminum-modified cathode of this invention, this compound can be perfectly adapted to the high-voltage battery operating system, significantly improving the structural stability, high-temperature storage performance and ultra-long cycle life of the battery under high-voltage conditions.

[0061] In one embodiment, the electrolyte further includes a lithium salt, which includes one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium difluorodioxalatophosphate, lithium tetrafluorooxalatophosphate, lithium tri(oxalato)phosphate, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(fluorosulfonyl)imide (LiFSI).

[0062] The aforementioned lithium salts are highly compatible with the aluminum-modified cathode, isocyanate-based silane co-solvent, and cyclic carbonyl additives of this invention, achieving synergistic optimization of the system within a ratio range of 0.03 ≤ X / (A+B) ≤ 0.035. Fluorine-based lithium salts effectively improve the ionic conductivity of the electrolyte while participating in interfacial film formation, generating stable fluoride components, enhancing the density of the SEI / CEI film, and suppressing electrolyte decomposition side reactions. Boronate and oxalate-based lithium salts further passivate the electrode interface, suppressing cathode metal dissolution and oxygen evolution, and improving the flexibility and high-temperature stability of the interfacial film. Sulfonylimide-based lithium salts have high dissociation and strong oxidation resistance, reducing battery polarization and improving rate charge / discharge performance. Using these lithium salts alone or in combination can complement and synergize with the siloxane inorganic framework and carbonyl organic film-forming system, further stabilizing the electrode interface structure, reducing irreversible capacity loss during long-term cycling, and effectively improving the battery's cycle stability and high-temperature storage performance.

[0063] In one embodiment, the electrolyte further includes a solvent comprising one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), methyl propyl carbonate (MPC), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate, ethyl butyrate, γ-butyrolactone (GBL), and δ-valerolactone (DVL).

[0064] The aforementioned carbonate, carboxylic acid ester, and lactone solvents exhibit excellent compatibility with the isocyanate-based silane co-solvent, cyclic carbonyl additive, and lithium salt system of this invention, synergistically optimizing the physicochemical properties and interfacial compatibility of the electrolyte within a defined ratio range. Specifically, the chain carbonate solvent has low viscosity and good wettability, effectively improving electrolyte flowability and ion migration rate, and reducing battery polarization; the short-chain carboxylic acid ester solvent further improves the low-temperature wettability and solubility of the electrolyte, optimizing the battery's low-temperature charge-discharge performance; and the lactone solvent has a high dielectric constant, promoting complete lithium salt dissociation and improving the electrolyte's ionic conductivity. This solvent system exhibits excellent chemical stability, avoiding adverse reactions with silane co-solvents and aluminum-modified cathodes. It can work in conjunction with the siloxane inorganic framework and nitrogen-containing organic polymer interfacial film system to maintain the integrity and stability of the electrode interface, reduce continuous solvent decomposition and loss, and minimize interfacial side reactions, synergistically improving the battery's rate performance, long-cycle stability, and high and low temperature storage performance.

[0065] In one embodiment, the pure silicon particles are deposited on the surface of the negative electrode current collector to form the negative electrode active material layer.

[0066] The pure silicon particles are directly deposited on the surface of the negative electrode current collector to form a layer of active material. This structural design can significantly improve the electronic conduction efficiency and interfacial bonding strength of the electrode, effectively reduce contact resistance, and avoid the problem of excessively high proportion of inactive components due to the introduction of binders and conductive agents in traditional slurry coating processes. At the same time, by controlling the deposition thickness and morphology (such as nanopillars, porous films, or gradient structures), expansion space can be reserved locally to alleviate the mechanical stress on the current collector caused by the huge volume change of silicon during charging and discharging, and suppress the peeling and pulverization of the active layer. Thus, while maintaining a high specific capacity (close to the theoretical value of 4200 mAh / g), the cycle stability and first coulombic efficiency are significantly improved, providing an effective technical path for constructing a binder-free silicon-based negative electrode with high energy density and long life.

[0067] In one embodiment, another aspect of the present invention provides an electrical device including the battery described above.

[0068] Specifically, the aforementioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.

[0069] The beneficial effects of the present invention will be further illustrated below with reference to the embodiments.

[0070] To make the inventive objectives, technical solutions, and beneficial effects of this invention clearer, the invention is further described in detail below with reference to embodiments. However, it should be understood that the embodiments of this invention are merely for illustrative purposes and not for limiting the invention, and the embodiments are not limited to those given in the specification. Materials not specified in the embodiments were prepared under conventional conditions or according to the conditions recommended by the material supplier.

[0071] Furthermore, it should be understood that the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps, does not preclude the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps, unless otherwise stated. It should also be understood that the combined connection relationship between one or more devices / apparatus mentioned in this invention does not preclude the existence of other devices / apparatus before or after the combined devices / apparatus, or the insertion of other devices / apparatus between these explicitly mentioned devices / apparatus, unless otherwise stated. Moreover, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not for limiting the order of the method steps or limiting the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention.

[0072] In the following embodiments, the reagents, materials and instruments used, unless otherwise specified, are commercially available or can be obtained through synthesis methods known in the art.

[0073] Table 1. Design of battery parameters for Examples 1-13 and Comparative Examples 1-10; Note: Formula 1-1 is cyclopentanone, Formula 1-2 is 1,4-butyrolactone, Formula 1-3 is ethylene carbonate, Formula 1-4 is 3-cyclopenten-1-one, Formula 1-5 is vinylene carbonate; Formula 2-1 is 3-isocyanate propyltriethoxysilane, Formula 2-2 is 3-isocyanate propyltrimethoxysilane.

[0074] Example 1 This embodiment illustrates the negative electrode sheet and battery disclosed in this invention; it includes the following operational steps: Preparation of positive electrode: A positive electrode slurry was prepared by mixing lithium cobalt oxide (LCO), conductive agent CNT, and binder PVDF in NMP solvent at a ratio of 97:1.5:1.5. The positive electrode slurry was coated onto aluminum foil with a safety primer. After drying, die-cutting, sheet making, welding tabs and attaching adhesive, a positive electrode sheet that meets the requirements was obtained. The aluminum content is shown in Table 1.

[0075] Preparation of negative electrode: Pure silicon particles are etched and deposited onto copper foil, and after drying, die-cutting, sheet making, and welding tabs and applying adhesive, a negative electrode sheet that meets the requirements is obtained.

[0076] Electrolyte preparation: Lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solvent consisting of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a mass ratio of 1:2:1 to obtain an electrolyte with a concentration of 1 mol / L.

[0077] Prepared in an argon atmosphere with a water content of <10ppm, the co-solvent, additives, and lithium salt were added to a solvent of EP and PP in a mass ratio of 3:7. The content of the co-solvent A% and the content of the additive B% are shown in Table 1.

[0078] Preparation of the diaphragm: PE porous polymer film is used as the membrane substrate; Battery manufacturing: The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes for isolation. They are then wound to form a battery cell. The cell is placed in a pre-formed aluminum-plastic film to complete the top and side sealing. After high-temperature baking, electrolyte injection, settling, formation, capacity testing, and other processes, the battery is obtained.

[0079] Example 2-13 Examples 2-13 illustrate the battery disclosed in this invention, including most of the operating steps in Example 1, with the following differences: The battery parameters shown in Table 1 are used.

[0080] Comparative Examples 1-10 Comparative Examples 1-10 are used to illustrate the battery disclosed in this invention, including most of the operating steps in Example 1, the difference being: The battery parameters shown in Table 1 are used.

[0081] Performance testing The following performance tests were performed on the batteries prepared in Examples 1-13 and Comparative Examples 1-10: 25℃ Cycling: At 25℃, charge to 4V at 1.5C, then charge to 4.3V at 0.7C constant current and constant voltage, cut off at 0.05C, rest for 5 minutes, discharge to 2.8V at 0.5C, rest for 5 minutes, cycle 200 times, and record the capacity retention rate after 200 cycles; 45℃ Cycling: At 25℃, charge to 4V at 1.5C, then charge to 4.2V at 0.7C constant current and constant voltage, cut off at 0.05C, rest for 5 minutes, discharge to 2.8V at 0.5C, rest for 5 minutes, cycle 200 times, and record the capacity retention rate after 200 cycles; Storage at 60℃: Let stand for 5 minutes at 25±2℃; charge to 4.2V with constant current and constant voltage at 0.5C, and record the initial thickness T0; store at 60℃ for 7 days and observe whether the cell produces gas.

[0082] The test results are shown in Table 2.

[0083] Table 2 Battery Electrochemical Performance Comparing Examples 1-5 and Comparative Examples 1-2, it can be seen that when the value of A is in the range of 2-20, the co-solvent can effectively participate in the formation of the SEI film on the negative electrode surface, constructing a dense and stable solid electrolyte interface layer on the surface of the pure silicon negative electrode, suppressing the volume expansion effect of silicon particles during charging and discharging. Simultaneously, the co-solvent and the main solvent of the electrolyte work synergistically to maintain the electrochemical window stability of the electrolyte. The battery's 25°C cycle capacity retention rate is between 86.21% and 86.39%, the 45°C cycle capacity retention rate is between 82.95% and 83.11%, and the 60°C storage expansion rate is between 12.31% and 12.45%, indicating excellent overall electrochemical performance. When the value of A is less than 2, the co-solvent content is insufficient, resulting in... The method of forming a complete protective SEI film on the negative electrode surface leads to continuous decomposition of the electrolyte and pulverization of silicon particles. The battery's cycle capacity retention rate at 25°C drops to 56.17%, at 45°C it drops to 53.99%, and the storage expansion rate at 60°C is 13.02%, resulting in a significant decrease in battery cycle performance and high-temperature storage performance. When the value of A is greater than 20, excessive co-solvent leads to an overly reactive electrolyte system, causing intensified side reactions and a significant increase in gas production. The battery's cycle capacity retention rate at 25°C drops to 56.19%, at 45°C it drops to 54.02%, and the storage expansion rate at 60°C reaches as high as 25.25%. At the same time, excessive co-solvent also damages the stability of the positive electrode interface, leading to a severe decrease in cycle performance.

[0084] Comparing Examples 1, 6-9, and Comparative Example 3, it is evident that when one of the following co-solvents—cyclopentanone, 1,4-butyrolactone, ethylene carbonate, 3-cyclopenten-1-one, and vinylene carbonate—is used, the aforementioned compounds possess suitable dipole moments and reduction potentials. They can preferentially reduce and decompose on the negative electrode surface to form a stable SEI film, effectively accommodating volume changes in silicon particles. The battery's cycle capacity retention at 25°C is between 86.04% and 88.57%, at 45°C it is between 82.77% and 85.08%, and the storage expansion rate at 60°C is 11.58%. Between 12.63% and 12.63%, the battery exhibits excellent overall electrochemical performance. However, in the absence of additives, the electrolyte lacks cyclic carbonyl compounds that can effectively form a film on the negative electrode surface, preventing the effective formation of the SEI film. This leads to continuous decomposition of the electrolyte in the main solvent, a continuous increase in the negative electrode interface impedance, severe degradation of cycle performance, and a significant increase in gas production. Consequently, the battery's 25°C cycle capacity retention rate drops to 55.51%, its 45°C cycle capacity retention rate drops to 52.19%, and its 60°C storage expansion rate reaches as high as 23.19%, resulting in a significant decrease in both cycle performance and high-temperature storage performance.

[0085] Comparing Examples 1, 5, 10-12, and 4-5, it can be seen that when the value of B is in the range of 0.5-2, the additive (isocyanate silane compound) can form a dense protective film on the positive electrode surface, inhibiting side reactions between the positive electrode active material and the electrolyte. Simultaneously, its decomposition products can migrate to the negative electrode surface to replenish the damaged SEI film. The battery's 25°C cycle capacity retention rate is between 85.81% and 86.39%, the 45°C cycle capacity retention rate is between 82.56% and 82.98%, and the 60°C storage expansion rate is between 12.31% and 12.89%, indicating excellent overall electrochemical performance. When the value of B is less than 0.5, the additive content is insufficient, failing to form a complete protective film on the positive electrode surface. This leads to increased dissolution of transition metal ions from the positive electrode and continuous electrolyte consumption, resulting in a decrease in the 25°C cycle capacity retention rate to 80.47% and the 45°C cycle capacity retention rate to 62.16%. At 60°C, the storage expansion rate is 13.14%, and the battery cycle performance is significantly reduced. When the value of B is greater than 2, the excess additive will form an excessively thick film on the positive electrode surface, increasing the interfacial impedance and hindering lithium-ion transport. At the same time, the excess additive may undergo polymerization side reactions, generating gas and an impedance layer. The battery's cycle capacity retention rate at 25°C drops to 75.43%, the cycle capacity retention rate at 45°C drops to 72.12%, and the storage expansion rate at 60°C is 13.11%, indicating a significant deterioration in battery cycle performance and rate performance.

[0086] Comparative Examples 1, 13 and 6 show that when the additive is either 3-isocyanate propyltriethoxysilane or 3-isocyanate propyltrimethoxysilane, the above compounds all contain isocyanate groups (-N=C=O). These groups have high reactivity and can preferentially oxidize and decompose on the positive electrode surface to form a dense positive electrode electrolyte interface film (CEI), effectively inhibiting the dissolution of transition metal ions and the oxidative decomposition of the electrolyte. The siloxane framework structures of the two silane compounds exhibit good thermal stability and film-forming properties, and the siloxane segments can adapt to volume changes during charge and discharge. The battery's cycle capacity retention rate at 25℃ is between 85.90% and 86.39%, at 45℃ it is between 82.67% and 82.98%, and at 60℃ it is between 12.31% and 12.67%, demonstrating excellent overall electrochemical performance. However, in the absence of additives, the positive electrode surface lacks a protective CEI film, leading to the extensive dissolution and migration of transition metal ions (such as cobalt and nickel) to the negative electrode, which disrupts the integrity of the SEI film and causes a sharp decline in cycle performance. The battery's cycle capacity retention rate at 25℃ drops to 75.54%, at 45℃ it drops to 52.23%, and at 60℃ it is 13.08%, indicating a significant decrease in cycle performance.

[0087] Comparing Examples 1-5 and Comparative Examples 7-9, it can be seen that when the value of X is in the range of 0.1-1, aluminum can form an effective Al-O protective layer on the surface of the positive electrode particles, which not only ensures the normal insertion and extraction of lithium ions, but also provides sufficient structural stability. The battery's cycle capacity retention rate at 25°C is between 86.21% and 86.39%, the cycle capacity retention rate at 45°C is between 82.95% and 83.11%, and the storage expansion rate at 60°C is between 12.31% and 12.45%, indicating excellent overall electrochemical performance. When the value of X is less than 0.1, the aluminum content is insufficient, resulting in limited protection. The positive electrode structure gradually degrades during cycling, and the battery's 25°C cycle capacity retention drops to 65.59%, 45°C cycle capacity retention drops to 62.34%, and the 60°C storage expansion rate is 15.02%, significantly reducing the battery's cycle performance. When the value of X is greater than 1, excessive aluminum forms an excessively thick insulating Al2O3 layer on the positive electrode surface, hindering lithium-ion transport and increasing interface impedance. The battery's 25°C cycle capacity retention drops to 65.65%, 45°C cycle capacity retention drops to 62.40%, and the 60°C storage expansion rate is 15.96%, leading to significant degradation in rate performance and cycle performance. When the value of X is 0, the battery's 25°C cycle capacity retention drops to 65.69%, 45°C cycle capacity retention drops to 62.45%, and the 60°C storage expansion rate is as high as 18.91%, severely degrading the battery's cycle performance and high-temperature storage performance.

[0088] Comparing Examples 1-13 and Comparative Examples 7-8, it can be seen that when the value of X / (A+B) is in the range of 0.03-0.035, the aluminum protection on the positive electrode surface and the co-solvent / additive protective film on the negative electrode surface achieve the best synergistic balance. The positive electrode structure is stable, the negative electrode SEI film is intact, the battery's cycle capacity retention rate at 25℃ is between 85.81% and 88.57%, the cycle capacity retention rate at 45℃ is between 82.56% and 85.08%, and the storage expansion rate at 60℃ is between 11.58% and 12.89%, indicating excellent overall electrochemical performance of the battery. When the value of X / (A+B) is less than 0.03, the aluminum content is too low relative to the amount of co-solvent and additives, resulting in insufficient positive electrode protection, severe dissolution of transition metals, and intensified oxidative decomposition of the electrolyte on the positive electrode side, leading to a significant increase in gas production. The battery's 25°C cycle capacity retention rate drops to 65.59%, its 45°C cycle capacity retention rate drops to 62.34%, and its 60°C storage expansion rate reaches as high as 15.02%, severely degrading the battery's cycle performance and high-temperature storage performance. When the value of X / (A+B) is greater than 0.035, the aluminum content is relatively too high. Although the positive electrode protection is sufficient, the excessively thick Al-O layer increases the interfacial impedance, and the imbalance between oxidation protection on the positive electrode side and reduction protection on the negative electrode side leads to a decrease in cycle performance. The battery's 25°C cycle capacity retention rate drops to 65.65%, its 45°C cycle capacity retention rate drops to 62.40%, and its 60°C storage expansion rate is 15.96%, significantly reducing the battery's cycle performance.

[0089] Comparing Example 1 and Comparative Example 10, it can be seen that when the electrolyte includes additives and the positive electrode active material includes aluminum, the crystal structure is stabilized and an Al-O protective layer is formed on the positive electrode side through aluminum doping. The additives in the electrolyte form a CEI film on the positive electrode surface, while the co-solvent and additives synergistically construct a stable SEI film on the negative electrode side. The positive and negative electrode interfaces are fully protected at the same time. The battery's cycle capacity retention rate at 25°C is 86.39%, the cycle capacity retention rate at 45°C is 82.98%, and the storage expansion rate at 60°C is 12%. The battery exhibits excellent overall electrochemical performance with a 31% reduction in capacity. However, when there are no additives in the electrolyte and the positive electrode active material does not include aluminum, the positive electrode lacks both structural stabilizers and surface protective films. This leads to the large-scale dissolution of transition metal ions, continuous decomposition and gas generation in the electrolyte, and incomplete SEI film on the negative electrode. Consequently, the positive and negative electrode interfaces degrade simultaneously, resulting in a decrease in the battery's 25°C cycle capacity retention rate to 55.78%, a 45°C cycle capacity retention rate to 72.53%, and a storage expansion rate as high as 22.89% at 60°C. This severely degrades the battery's cycle performance and high-temperature storage performance.

[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A battery, characterized in that, include: A positive electrode sheet, comprising a positive current collector and a positive active material layer disposed on the positive current collector, the positive active material layer comprising a positive active material, the positive active material being doped with and / or coated with aluminum; the mass content of aluminum in the positive active material layer is X %, the value of X being in the range of 0.1-1; A negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer disposed on both sides of the negative electrode current collector, the negative electrode active material layer comprising pure silicon particles; An electrolyte comprising a co-solvent and an additive; the co-solvent comprising a cyclic carbonyl compound, and the additive comprising an isocyanate silane compound; wherein the total mass of the electrolyte is denoted as 100%, the mass percentage of the co-solvent in the electrolyte is denoted as A%, where A ranges from 2 to 20; and the mass percentage of the additive in the electrolyte is denoted as B%, where B ranges from 0.5 to 2. The values ​​of A, B, and X satisfy the following conditions: 0.03≤X / (A+B)≤0.

035.

2. The battery according to claim 1, characterized in that, The value of A is in the range of 5-10.

3. The battery according to claim 1, characterized in that, The value of B is in the range of 0.8-1.

4. The battery according to claim 1, characterized in that, The cyclic carbonyl compounds include one or more of cyclopentanone, 1,4-butyrolactone, ethylene carbonate, 3-cyclopenten-1-one, and vinylene carbonate.

5. The battery according to claim 1, characterized in that, The chemical formula of the isocyanate silane compound is: Si(OR1)3-(R2)3-NCO; R1 and R2 are each independently selected from one of the C1-C6 alkyl groups.

6. The battery according to claim 5, characterized in that, The isocyanate silane compounds include one or more of 3-isocyanate propyltriethoxysilane and 3-isocyanate propyltrimethoxysilane.

7. The battery according to claim 1, characterized in that, The electrolyte further includes lithium salts, which include one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxaloyl)borate, lithium difluorophosphate, lithium difluorooxaloylborate, lithium difluorodioxaloyl phosphate, lithium tetrafluorooxaloyl phosphate, lithium tri(oxaloyl)phosphate, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide.

8. The battery according to claim 1, characterized in that, The electrolyte further includes a solvent, which includes one or more of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, γ-butyrolactone, and δ-valerolactone.

9. The battery according to claim 1, characterized in that, The pure silicon particles are deposited on the surface of the negative electrode current collector to form the negative electrode active material layer.

10. An electrical device, characterized in that, Includes the battery as described in any one of claims 1 to 9.